DEVELOPMENT OF A WEB-BASED FOUR TIER DIAGNOSTIC TEST TO IDENTIFY STUDENTS’ MISCONCEPTIONS IN PHYSICS - Yuliana, Ina; Artawan, Putu; Heny, Ajeng Purnama (Universitas Negeri Padang, 2025)
This study aims to develop a web-based four tier diagnostic test to identify students' physics misconceptions on heat and temperature. This research uses the Research and Development (R&D) method with the ADDIE development model which consists of five stages, namely analysis, design, develop, implementation, and evaluate. The research data includes quantitative data in the form of validator evaluations and qualitative data in the form of comments and suggestions given by validators and analysis of student answers. Based on the results of the feasibility validity test from media, design and material expert validation, this product shows a very feasible category to use. The results of the interpretation of student answers show that students experience misconceptions in all the questions given.